Exercise capacity benefit in relation to endogenous testosterone, coronary and central vascular physiology, and the Mediterranean regime in hypertensive males with erectile dysfunction. (14th October 2021) - Angelis, A; Aggeli, K; Dimitroglou, I; Ioakeimidis, N; Georgakopoulos, C; Zisimos, K; Aznaourides, K; Kakiouzi, V; Verveniotis, A; Crysochoou, C; Synodinos, A; Krommydas, A; et al.
Abstract: Background: The Mediterranean diet (Med-diet) benefits cardiovascular health, and erectile dysfunction (ED) often coexists in the hypertensive aging male population were endogenous testosterone (TT) typically declines. Coronary flow reserve (CFR) displays the ability of the coronary circulation to increase flow. Wave reflection amplification as expressed by augmentation index (AIx) exhibits a vital parameter of central vascular stiffness. Purpose: To investigate the possible benefits of the Med-diet in exercise capacity, central physiology, CFR and erectile ability in relation to endogenous TT in the middle aged male hypertensive population with ED. Methods: 250 hypertensive males (mean age 56 yo) with ED enrolled the study. All underwent a treadmill stress test (Bruce protocol). Exercise capacity was validated as metabolic equivalents (METs). We measured separately the CFR of the left anterior descending artery by an adenosine protocol (max dose 140μg/kg/min over 6 minutes). PW Doppler measurements were achieved at the middle/distal LAD segment under the guidance of color Doppler flow mapping. CFR was validated as ratio between peak diastolic flow velocity following drug infusion and rest. Ratios ≥2 are considered as non-ischemic response, higher values indicate microvascular coronary integrity. TT was measured on blood samples taken before 09:00 am. ED severity and adherence to the Med-diet were assessed by the SHIM-5 (range: 0–25) and the Med-diet (range: 0–55) scores. Higher values indicate a better erectile ability and Med-diet compliance respectively. Finally, central pulse pressure (cPP) and AIx were noninvasively estimated as parameters of central hemodynamic load and wave reflection amplification (Sphygmocor device). Results: In bivariate analysis METs were positively associated to the Med-diet, CFR, TT and the SHIM-5 score (all p<0, 005) and negatively to the AIx and cPP (both p<0, 025). There was also positive association of the Med-diet to the CFR, TT and the SHIM-5 score (p<0, 02) and negative to the AIx and cPP (p<0, 025). By linear regression analysis association of METs to TT, CFR and Med-diet remained significant after adjustment for age, BMI, diabetes mellitus, use of statins and smoking status (p<0, 005). We further subdivide our population according to the TT threshold of hypogonadism (≤3 ng/ml). Hypogonadism patients exhibit a lower exercise capacity comparing to the normal TT group (picture). Conclusion: The Med-diet regime benefits exercise tolerance and erectile performance in hypertensive males with ED by enhancing endogenous testosterone and so coronary and central vascular physiology. We strongly recommend this culinary preference promoting thus vascular health and the sense of well being. FUNDunding Acknowledgement: Type of funding sources: None.